Karakteritik Pasien Ginekologi di RSU Cut Meutia Aceh Utara Selama Pandemi Covid-19 Tahun 2020 - Iskandar - Iskandar (Jurnal Kedokteran Syiah Kuala, 2021)
Gynaecology literally means "the science of women" or science of woman, which is a branch of medical science that specifically studies and treats diseases of the female reproductive system. The scope of gynecology includes, among others, menstrual disorders and AUB, infectious diseases, tumors, post-treatment and so on. Uterine fibroids are the most common benign tumor found with a worldwide incidence of 20–35%.  This research is a descriptive study with the research design used is across-sectional studyconducted in the Gynecology Inpatient Room at the Cut Meutia Hospital, North Aceh. The study was conducted in June 2021 with a population and sample of all patients in the Gynecological Inpatient Room at the Cut Meutia Hospital North Aceh in 2020. The variables of this study were types of gynecological diseases which were divided into menstrual disorders, infections, benign tumors, malignant tumors and so on. Univariate analysis was used to describe the characteristics of the types of gynecological diseases that existed in the Gynecological Inpatient Room at the Cut Meutia Hospital North Aceh in 2020. The patients who were treated in the Gynecological Inpatient Room at the Cut Meutia North Aceh Hospital in 2020 were 70 patients who were divided into groups of menstruation disorders and AUB, infectious diseases, tumors and so on. The percentage of benign and post-operative tumors is the largest group of diseases, while infections and malignant tumors are the least. Uterine fibroids are the most common disease, followed by menstrual disorders (AUB), uterine prolapse, ovarian cysts and endometrial hyperplasia.